Patients and Healthcare Providers’ Attitudes and Perceptions of Drug-related Problems in Saudi Arabia - Alomi, Yousef Ahmed; Al-Shaibani, Awatif Saad; Ghadeer, Alfaisal; Alasmi, Njood Mohmmed (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the patients and healthcare providers’ attitudes and perceptions of drug-related problems in Saudi Arabia. Methods: It is a 4-months cross-sectional survey of drug-related problem information in Saudi Arabia. The study consisted of two-part a demographic data, and second part contained the questions about the knowledge of drug-related problems, the frequent occurrence, the type of medication-induced those problems, and the resources information used about the drug-related problem. American Society of Health System Pharmacist definitions of drug-related problems used. The 5-point Likert response scale system used. The survey distributed through social media. The questionnaire made of an electronic format, and it analyzed through survey monkey system. Results: The total responders were two hundred and one; the Saudi nationality was 188 (93.5%), and non-Saudi was 13 (6.5%) patient. The gender distribution was female 180 (89.6%), and the male was 21 (10.4%). The majority of them in age (18-44) 88% and located in Riyadh region 84 (41.8%) and Asir region 59 (29.4%). Of those 44 (22.1 %) were healthcare providers. The majority of responders showed good knowledge about medication non-compliance 150 (75.76%), and medication without indication 147 (73.1%), while an adequate revealed information of adverse drug reaction 128 (64%), and an indication without medication 124 (62%). The imperfect information found about drug interaction 75 (37.5%) and drug poisoning 89 (44.5%). The most frequent drug-related problems occurred with the patient last year at least once; it was drug noncompliance 142 (71.4%), indications without medication 100 (50%), and adverse medication events 80 (40%). The most resources information on drug-related problems used were the internet, medicine leaflet, and healthcare practitioners. Conclusion: Drug-related problems occurred at a high rate in Saudi patients. The knowledge of drug-related problems is not adequate. It is very demanding and comprehensive public education about medication and urgent implementation of the patient medications counseling program in Saudi Arabia.
Keywords: Patients; Healthcare providers; Attitudes; Perceptions; Drug-related problems; Saudi Arabia